Strategies to Optimise Long-term Memory in Learning Vocabulary - Sabrina Salsabila; Didik Santoso (Universitas Negeri Medan, 2024)
Optimizing long-term memory in vocabulary is a significant challenge for many university students. The author explores various strategies which include: (1) spaced repetition, (2) use of mnemonic devices, (3) contextual learning, (4) active use, (5) visual aids and mind mapping, (6) self-testing with mobile apps, and (7) associative learning. Each strategy is discussed in depth in current research. The findings show that a combination of several strategies, such as spaced repetition with memory practice, the use of verbal mnemonics, contextualized learning, and visual aids, can significantly improve vocabulary retention and language comprehension.